The making of precarity: an ethnography on precarious workers in Auckland, New Zealand - Marko Galič (Kōtuitui)
The following article focuses on the everyday struggles of precarious workers in Auckland, New Zealand. As an excerpt from an ethnography on lived precarity in Auckland City, it reveals structural constraints that precarious workers face daily. This includes insecure work, poverty, precarious housing and, consequently, living in a constant state of anxiety, stress and destroyed work-life balance. Structural constraints of precarious work create a state of precarity that goes beyond labour relations, revealing creation, reproduction and normalisation of precarity as a mode of domination and social control. In a short historical context, the article emphasises the existence of the Māori precariat and precarity among migrant workers that precedes neoliberal precarisation of labour and its imposition of precarity to broader segments of New Zealand society. Empirically, the article focuses on testimonies of precarious workers in Auckland, emphasising particular dimensions of precarious work and precarity.